Oral health status and reported oral health problems in people with intellectual disability: A literature review. Issue 3 (3rd July 2019) - Wilson, Nathan J.; Lin, Zhen; Villarosa, Amy; George, Ajesh
ABSTRACT: Background : People with intellectual disability (ID) experience poor oral health and are at greater risk of dental decay and periodontal diseases. This impacts on their general health and wellbeing. This review summarises the research literature about oral health status and contributing factors to poor oral health Method : We conducted a literature review using "intellectual disability" and "oral health" as our two core areas of focus. Results : People with ID had poorer oral health, greater numbers of tooth extractions, more caries, fewer fillings, greater gingival inflammation, greater rates of endentulism, and had less preventative dentistry and poorer access to services when compared to the general population. Anxiety during dental procedures was a key issue for females with ID. Conclusions : Further research is needed to identify, pilot and test appropriate and effective interventions that can reduce this preventable health disparity. The design of an ID-specific dental anxiety scale is another priority.